2014
DOI: 10.1371/journal.pcbi.1003797
|View full text |Cite|
|
Sign up to set email alerts
|

Multiscale Approach to the Determination of the Photoactive Yellow Protein Signaling State Ensemble

Abstract: The nature of the optical cycle of photoactive yellow protein (PYP) makes its elucidation challenging for both experiment and theory. The long transition times render conventional simulation methods ineffective, and yet the short signaling-state lifetime makes experimental data difficult to obtain and interpret. Here, through an innovative combination of computational methods, a prediction and analysis of the biological signaling state of PYP is presented. Coarse-grained modeling and locally scaled diffusion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…4648 Using transition path sampling of explicit solvent molecular dynamics simulations on the millisecond time scale, Vreede et al sought to examine conformational changes accompanying the transition to the PYP signaling state. 47 They concluded that formation of the signaling state involves unfolding of α -helical region 43–51, which in turn leads to solvent exposure of both Glu46 and the PCA chromophore.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4648 Using transition path sampling of explicit solvent molecular dynamics simulations on the millisecond time scale, Vreede et al sought to examine conformational changes accompanying the transition to the PYP signaling state. 47 They concluded that formation of the signaling state involves unfolding of α -helical region 43–51, which in turn leads to solvent exposure of both Glu46 and the PCA chromophore.…”
Section: Discussionmentioning
confidence: 99%
“…The results reported here unveil a structure transition far more dramatic than described by Vreede et al and likely involves unfolding of the 25-residue N-terminal domain. Subsequent efforts to characterize theoretically the signalingstate ensemble via a multiscale approach 48 concluded that their computational results differ from the experimental results reported by Kim et al and stated "More work is needed to understand this aspect of the PYP photo cycle. "…”
Section: ■ Discussionmentioning
confidence: 99%
“…Top-down Simulations of Amyloid Peptides Validate the Generality of Our Theory and Approach. For further tests, we simulated the aggregation of three amyloid peptides (27 peptides with a minimum separation of 30 Å between all of the peptides), including the GNNQQNY segment from the yeast prion protein Sup35 (PDBID: 1YJP), the amyloid-β (Aβ (16)(17)(18)(19)(20)(21)(22), PDBID: 2MXU), and the α-synuclein fragment (α-syn , PDBID: 2N0A). We measured the diffusion coefficients of the monomers for GNNQQNY peptide, Aβ (16)(17)(18)(19)(20)(21)(22), and α-syn at different stages in preparation for eq 4 (Figure 2 and Table S5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The serial multiscale method carries out modeling at different resolutions in sequence, which takes advantages of sampling efficiency at lower resolutions and detailed accuracy at higher resolutions. It has been applied to problems that are currently difficult to simulate with the AA models. A straightforward setup of serial simulations includes top-down modeling, which starts from the least detailed model and recovers the details until a fully atomistic model is obtained. However, serial top-down simulations have never been systematically tested with more than two resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…An additional local scale parameter, indicating the distance around a specific configuration presumably could be well approximated by a low-dimensional hyperplane tangent. LSDMap is applied in [43] and enhances the exploration of the configurational space as shown in [44]. More recent approaches to collective variable discovery work under a common variational approach for conformation dynamics (VAC) 45 and employ a combination of basis functions for defining the eigenfunctions to the backward Fokker-Planck operator.…”
Section: Introductionmentioning
confidence: 99%